2017
DOI: 10.1107/s1600576717000279
|View full text |Cite
|
Sign up to set email alerts
|

Energy-resolved small-angle neutron scattering from steel

Abstract: Recent progress of pulsed neutron sources has enabled energy‐resolved analysis of neutron attenuation spectra, which include information on neutron scattering. In this study, a new analysis technique for small‐angle neutron scattering (SANS) is demonstrated. A clear difference is observed in the neutron attenuation spectra between steels with different nanostructures; this difference can be understood as arising from attenuation due to SANS. The neutron attenuation spectra calculated from the corresponding SAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…A recent study has demonstrated that the neutron attenuation coefficient is proportional to the scattering intensity integrated in all solid angles [8]. Although this study discussed only a contribution of small-angle neutron scattering (SANS), this idea can be simply expanded to neutron diffraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated that the neutron attenuation coefficient is proportional to the scattering intensity integrated in all solid angles [8]. Although this study discussed only a contribution of small-angle neutron scattering (SANS), this idea can be simply expanded to neutron diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the ref. [8], conventional analytical techniques for the neutron diffraction of the liquid phases can be also applied to the neutron transmission spectra. Such application enables to obtain the structural information about the liquid phases from the neutron transmission images.…”
Section: Resultsmentioning
confidence: 99%
“…A contribution from SANS can be also observed in the neutron transmission and effective for the characterization of the precipitates as well as the application to the neutron imaging experiments. 18,19) While these neutron transmission techniques are frequently used with dedicated analysis codes such as RITS (Rietveld Imaging of Transmission Spectra) in the neutron imaging experiments, they can also be applied to various experiments without such software. The characteristic shapes of the neutron transmission spectra allow direct understanding of structural information similar to the relation between Bragg peaks and crystal structures.…”
Section: Characterization Of Deformation By Cold Rolling In Ferritic Steel Containing Cu Particles Using Neutron Transmission Analysismentioning
confidence: 99%
“…In addition, neutron transmission measurements are also useful for the microstructural characterization. 1,[12][13][14][15][16][17][18][19] The scattered neutrons by diffraction and SANS can be observed as the decrease in the neutron transmission. The wavelength dependence (spectrum) of the decrease in the neutron transmission by neutron diffraction is well-known as Bragg-edge transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, note that there are also small portions of magnetic Bragg scattering component [12,13] and small-angle scattering component [14,15] in the coherent elastic scattering, actually.…”
Section: Neutron Transmission and Total Cross-sectionmentioning
confidence: 99%